Estimation of Internal Radiation Doses for Occupational Workers Due to 131I Radionuclide by Using MONDAL Software (Bangladesh Journal of Nuclear Medicine, 2022)
Radioactive iodine (131I) is most commonly used radionuclide in nuclear medicine field for diagnosis and therapy purposes. 131I is used in treatment of thyrotoxicosis & thyroid cancer. While administrating patients, occupational workers tends to get exposed to radioactivity. Thus an evaluation of worker effective dose is required to maintain it within 20 mSv/y limit according to ICRP. To assist the evaluation, thyroid radioactivity monitoring program has been chosen for the measurement of effective doses of occupational workers of 131I radionuclide. A software MONDAL-3 has been used to calculate the radionuclide intake, distribution, retention & other biokinetic behavior of the radionuclide. From MONDAL-3 excretion rate at measurement day, activity of intake, effective dose, excretion curves for 131I radionuclide are obtained by using pre measured thyroid activity data of real life occupational worker. By using retention curves, tissue equivalent dose and effective doses upto 50 years have been calculated. The average effective dose of all workers is found to be within regulatory dose limit set by ICRP.Bangladesh J. Nuclear Med. 23(1&2): 40-45, 2020